2010
DOI: 10.12968/bjon.2010.19.7.47432
|View full text |Cite
|
Sign up to set email alerts
|

Sacral nerve stimulation for the management of faecal incontinence

Abstract: Faecal incontinence is a distressing and embarrassing problem that can have a profound affect upon quality of life. The true incidence is unclear, as figures from studies vary depending on the definition used and the population studied. Data from a comprehensive study by Nelson et al (1995) found that 2.2% of the population has faecal incontinence and 10% of those have severe symptoms. The incidence increases with age (Perry, 2002) This article sets out to highlight the importance of assessment along with expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Seventy‐two full‐text articles were assessed in detail and a further 11 studies were excluded: one study used mixed urinary and faecal incontinence indications for implantation, one study did not have original clinical outcome data, two studies had PNE data only, three studies had no documented baseline of the chosen outcome measures, two studies had no follow‐up terms documented, one study did not clearly document the results of the chosen outcome measures and one study was excluded as it exactly duplicated the data set of another included study; further clarification was not possible. This left 61 SNS studies that were appropriate for inclusion; in order to present data on ITT analysis, studies were separated into those that included all consecutive patients (including failures) in whom PNE was attempted (46 studies) ( Table ) and those that only reported outcomes of positively responding patients to the test phase (15 studies) ( Table ). Patients who were still awaiting permanent implantation despite a successful PNE were excluded from the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Seventy‐two full‐text articles were assessed in detail and a further 11 studies were excluded: one study used mixed urinary and faecal incontinence indications for implantation, one study did not have original clinical outcome data, two studies had PNE data only, three studies had no documented baseline of the chosen outcome measures, two studies had no follow‐up terms documented, one study did not clearly document the results of the chosen outcome measures and one study was excluded as it exactly duplicated the data set of another included study; further clarification was not possible. This left 61 SNS studies that were appropriate for inclusion; in order to present data on ITT analysis, studies were separated into those that included all consecutive patients (including failures) in whom PNE was attempted (46 studies) ( Table ) and those that only reported outcomes of positively responding patients to the test phase (15 studies) ( Table ). Patients who were still awaiting permanent implantation despite a successful PNE were excluded from the analysis.…”
Section: Resultsmentioning
confidence: 99%